Enhancement of the laser-driven proton source at PHELIX. (2020) - Hornung, J.; Zobus, Y.; Boller, P.; Brabetz, C.; Eisenbarth, U.; Kühl, T.; Major, Zs.; Ohland, J. B.; Zepf, M.; Zielbauer, B.; Bagnoud, V.
Abstract : We present a study of laser-driven ion acceleration with micrometre and sub-micrometre thick targets, which focuses on the enhancement of the maximum proton energy and the total number of accelerated particles at the PHELIX facility. Using laser pulses with a nanosecond temporal contrast of up to 10^-12 and an intensity of the order of 10^20 W/cm^2, proton energies up to 93 MeV are achieved. Additionally, the conversion efficiency at 45^° incidence angle was increased when changing the laser polarization to p, enabling similar proton energies and particle numbers as in the case of normal incidence and s-polarization, but reducing the debris on the last focusing optic.